Clinical screening tool for early detection of congenital heart disease in children living at high altitude - Gautam, Abhinav; Bhardwaj, Parveen; Roach, Vipin; Sachdeva, Amit; Rana, Drishti (International Journal of Contemporary Pediatrics, 2024)
Background: Congenital heart diseases (CHD) have a high morbidity and mortality and its early detection is critical. The aim of the study is to develop a clinical screening tool for early detection of children with congenital heart disease at high altitude. Methods: This was a hospital based cross sectional study. All children between age 0 to 1 year visiting the OPD and admitted in indoor services of pediatrics with suspected heart disease based on pre-defined clinical criteria were evaluated for development of clinical screening tool for prediction of presence of CHD using parameters; heart rate (HR), respiratory rate (RR), ratio of HR/RR, pulse oximetry, presence of precordial pulsations and murmurs. Then diagnostic performance of these tools was calculated by using ECHO as a gold standard test. Results: A total of 102 study participants were included in our study. Among the total, 79 (77.5%) had underlying CHD. Result was considered positive if any of them was pres ent. In children age less than one year living at high altitude suspected to have high risk for presence of CHD and/or arterial oxygen saturation of less than 87.2%, this screening tool has sensitivity of 78.79% and specificity of 66.67%. Conclusions: This study concluded that combination of screening tools along with pulse oximetry in the community settings of developing countries are better in early detection and timely management of CHD than using these tests/ parameters alone.